Middle Meningeal Artery Embolization for the Treatment of Bilateral Chronic Subdural Hematoma - Wei, Qi; Fan, Gangxian; Li, Zhenzhu; Wang, Qingbo; Li, Ke; Wang, Chao; Li, Zefu (Frontiers in Neurology, 2021)
Background: Bilateral chronic subdural hematoma (bCSDH) is a frequent condition commonly linked to the need for retreatment; however, the reason for this high retreatment rate remains unclear. The middle meningeal artery (MMA) was found to have a relationship with the occurrence and development of chronic subdural hematomas. This study examines a possible method to reduce bCSDH recurrence using bilateral MMA embolization combined with bilateral burr-hole drainage. Materials and Methods: Ten patients with bCSDH who underwent bilateral MMA embolization combined with bilateral burr-hole drainage at our hospital between June 2018 and May 2020, were retrospectively analyzed. Patients' clinical information, prognoses, imaging results, as well as surgical results were documented and analyzed. Results: Ten patients were diagnosed with bCSDH with no comorbid brain diseases. They underwent bilateral MMA embolization combined with bilateral burr-hole drainage. We embolized the MMA immediately before burr hole drainage successfully and employed angiography to validate these results. All the patients attained relief of symptoms without adverse events, and no re-expansion or relapse was reported in the follow-up computed tomography. Conclusion: Bilateral MMA embolization combined with bilateral burr-hole drainage is an available treatment for patients with bCSDH and may have the potential for preventing recurrence.